Latin American Middle Classes: The Distance between Perception and Reality - Eduardo Lora; Deisy Johanna Fajardo (Inter-American Development Bank (IDB), 2011)
The main contribution of this paper with respect to previous work is the use of data on subjective perceptions to identify the Latin American middle classes. This paper provides a set of comparisons between objective and subjective definitions of middle-class using data from the 2007 World Gallup Poll. Seven objective income-based definitions of social class are contrasted with a self-perceived social status measure. Mismatches between the objective and the subjective classification of social class are the largest when the objective definition is based on median incomes. Mismatches result from the fact that self-perceived social status is associated not just with income, but also with personal capabilities, interpersonal relations, financial and material assets, and perceptions of economic insecurity. Objective definitions of the middle class based on absolute incomes provide the lowest mismatches and the most accurate differentiation of the middle class from other classes.
Keywords: D3; D6; I3; 330